Age, growth, mortality, and population characteristics of the red snapper (Lutjanus malabaricus) in the Timor Sea waters, Indonesia - SUSY HERWATY; ACHMAR MALLAWA; NAJAMUDDIN NAJAMUDDIN; MUKTI ZAINUDDIN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Herwaty S, Mallawa A, Najamuddin, Zainuddin M. 2023. Age, growth, mortality, and population characteristics of the red snapper (Lutjanus malabaricus) in the Timor Sea waters, Indonesia. Biodiversitas 24: 2217-2224. Red snapper (Lutjanus malabaricus Bloch & Schneider 1801) is a fishery resource with export commodities, high market demand is suspected of causing overfishing and a decrease in stocks, thus threatening its sustainability. This study aims to analyze the red snapper's age, growth, mortality, and population characteristics. Fish samples were collected at the Oeba Fish Landing Base Kupang from April to June 2020. The data analysis were as follows: the descriptively analyzed size structure, age group using the Bhattacharya method, growth parameter values (L? and K) based on the von Bertalanffy equation, and natural mortality using the Pauly and Y/R using the Beverton and Holt methods. The results of the red snapper observation are as follows: the smallest size at 12.8 cm (FL), the largest size at 72.8 cm (FL), the average length at 42.03 cm (FL) ± 16.03, the growth parameter value (L?)=99.40 cm (FL), (K)=0.51 year-1, t0=-0.23018 year-1, the population consisted of two and three age groups, the total mortality value (Z) 1.98 year-1, natural mortality (M) 0.84 year-1, fishing mortality (F) 1.14 year-1, and exploitation rate (E) 0.58 year-1. The actual Y/R value was 0.049, and the relative Y/R was 0.060 grams recruit-year-1. The fishing mortality is higher than the natural mortality value; a high exploitation value (E>0.5) indicates that over-exploitation and stock conditions are unhealthy. The results of this study can be used as a reference in managing red snapper resources in the future.